The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1108/nlw-04-2014-0033
|View full text |Cite
|
Sign up to set email alerts
|

What threatens public libraries? The viewpoints of library directors in Sweden

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…This remark is actually valid at all levels of the organization. Managers are closest to the politicians, and research has shed light on the complexity of this relation (Evjen, ; Michnik, ). It is not surprising that research has shown that library managers emphasize “the importance of effective engagement with key decisions makers” (Goulding, Walton, & Stephens, , p.114).…”
Section: To Librarize Is Politicalmentioning
confidence: 99%
“…This remark is actually valid at all levels of the organization. Managers are closest to the politicians, and research has shed light on the complexity of this relation (Evjen, ; Michnik, ). It is not surprising that research has shown that library managers emphasize “the importance of effective engagement with key decisions makers” (Goulding, Walton, & Stephens, , p.114).…”
Section: To Librarize Is Politicalmentioning
confidence: 99%
“…Predictions that the Internet and access to digital information would render libraries obsolete have thus far been unfounded (Gisolfi 2015;Dudley 2013;Latimer 2011;Worpole 2004). Nevertheless, the sands are shifting and embracing digital media is seen as crucial to maintaining the relevance and legitimacy of the library (Michnik 2014); reconceptualising services in line with the needs of the 21st century patron demands that libraries challenge convention (Carroll and Reynolds 2014). New library programmes include a broad spectrum of uses such as community facilities, creative and recreational spaces, health and well-being services, council helpdesks, gallery and museum spaces, cafés, cultural entertainment spaces, entrepreneurial start-up facilities and meeting rooms.…”
Section: Throwing Out the Books?mentioning
confidence: 99%
“…During 2010 Amazon reported that e-books had outsold both hardbacks and paperbacks (Dudley 2013), and between 2012 and 2014 sales of printed books dropped by six percent (BBC 2014). A 2011 study of perceived threats to public libraries in Sweden cited a decreased interest in reading and increasing availability of digital media as major concerns (Michnik 2014).…”
Section: Throwing Out the Books?mentioning
confidence: 99%
See 1 more Smart Citation
“…The nature and needs of library users have shifted, and information and communication technologies (ICTs) have had an impact on many technical and organizational areas, which are also associated with users’ needs and perceptions. Both of these factors have led to new roles and new areas for the public library and, consequently, to new expectations (Michnik, 2014).…”
Section: Introductionmentioning
confidence: 99%